Effects of Newtonian heating and heat generation on magnetohydrodynamics dusty fluid flow between two parallel plates - Ali, Farhad; Ali, Gohar; Khan, Arshad; Khan, Ilyas; Eldin, Elsayed Tag; Ahmad, Matin (Frontiers in Materials, 2023)
A equitably complicated phenomena, the Casson dusty fluid and Newtonian heating effect finds usage in a wide variety of engineering and product-making fields. For instance, dusty fluids are employed in nuclear-powered reactors and gas freezing systems to reduce heat of the system. To ascertain the impact of Newtonian heating on Casson dusty fluid flow, the current study intends to do so. The dusty Casson fluid's two-phase MHD fluctuating flow is taken into account between two parallel plates. It is believed that the dust particles in the Casson fluid are spherical and evenly dispersed. Additionally thought about were heat production and absorption. The motion of the fluid is due to the motion of the right plate with free stream velocity . In order to depict the flow regime, partial differential equations are used. Assumed periodic solutions are used to solve the system of partial differential equations (Poincare-Light Hill Technique). Additionally, a graphic representation of parametric effect on the velocity and temperature profiles is provided. Additionally estimated in tabular form are skin friction and rate of heat transfer, two crucial fluid parameters for engineers. It is determined that when the magnetic field increases, the fluid's velocity decreases. The heating on the plate is impacted by the Newtonian heating phenomenon.